Routledge handbook of human rights and disasters - Zorzi Giustiniani, Flavia (Routledge studies in humanitarian action, 2018)
The Routledge Handbook of Human Rights and Disasters provides the first comprehensive review of the role played by international human rights law in the prevention and management of natural and technological disasters. Each chapter is written by a leading expert and offers a state-of-the-art overview of a significant topic within the field. In addition to focussing on the role of human rights obligations in disaster preparedness and response, the volume offers a broader perspective by examining how human rights law interacts with other legal regimes and by addressing the challenges facing humanitarian organizations.--